Planning identification experiments for cell signaling pathways: an NF[kappa]B case study - Fujarewicz, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Mathematical modeling of cell signaling pathways has become a very important and challenging problem in recent years. The importance comes from possible applications of obtained models. It may help us to understand phenomena appearing in single cells and cell populations on a molecular level. Furthermore, it may help us with the discovery of new drug therapies. Mathematical models of cell signaling pathways take different forms. The most popular way of mathematical modeling is to use a set of nonlinear ordinary differential equations (ODEs). It is very difficult to obtain a proper model.
Keywords: cell signaling pathways; experiment design; parameter estimation